On Objects and Material Devices in the Organisational Responses to Institutional Pluralism: Insights from Economies of Worth - Daudigeos, Thibault; Valiorgue, Bertrand (Management international / International Management / Gestiòn Internacional, 2018)
This research note contributes to the conceptual development of neo-institutional theory by applying the work of scholars associated with the economies-of-worth research stream to enhance understanding of how objects and material devices contribute to stabilising coordination processes when multiple principles of action coexist within a single organisation. We demonstrate that, depending on the responses to different principles of action constructed by an organisation and its members, different objects and material devices are involved. Specifically, we use empirical examples to highlight three categories of objects and material devices: specific, composite and settlement objects.